La plastica: un mondo da scoprire - Fortunato, Laura; De Donno, Maria Consiglia; Scippa, Sabrina; Giannuzzi, Vita Lina (Chimica nella Scuola, 2022)
The knowledge of plastic and damages of its use is fundamental nowadays as is the knowledge of correct recycling. Lately we talk a lot about bioplastics, but not everyone knows their nature and their use. Within the learning teaching unit related to the knowledge of plastic and its recycling, the students of II A AFM and II B AFM classes of the Cezzi De Castro Moro Institute of Maglie (LE) conducted a survey aimed, through a statistical analysis of the data collected, to evaluate the level of knowledge about these issues.